Pla/Cao Nanocomposites with Antimicrobial and Photodegradation Properties - Ortiz-Nunez, J; Zapata-Ramirez, P; Loyo-Davila, C; Moreno-Serna, V (Elsevier Ltd, 2022)
CaO nanoparticles sized ca. 26 nm were organically modified with oleic acid (Ol-CaO), and both were incorporated into PLA at concentrations of 5 and 8 wt.% by a melting process. Modification of nanoparticles improved the distribution into PLA, as seen by transmission electron microscopy (TEM). Thermal analysis revealed that the presence of Ol-CaO in the PLA matrix promoted a decrease ca. 13% in the glass transition temperature (Tg). The thermal stability of the PLA/Ol-CaO decreased ca. 23% compared to the neat PLA due to the catalytic activity from nanoparticles, while Vickers Microhardness (HV) for nanocomposites PLA/Ol-CaO increased ca. 9%, compared with the neat PLA, due to the good dispersion of modified-surface Ol-CaO nanoparticles in PLA. PLA/Ol-CaO nanocomposites reached 99.9% of antimicrobial effectiveness against E. coli for nanoparticles content above 8 wt.%. From photodegradation tests under irradiation during five days, it was verified that the presence of CaO nanoparticles accelerated the photodegradation of the polymer matrix nanoparticles into PLA promoted a decreasing ca. 13% of Tg and an increase in the degree of crystallinity (Xc) (ca. 7%), compared to PLA/CaO without irradiation. Besides, the viscosity molecular weight (M¯v) of PLA/CaO showed a higher decrease than neat PLA after irradiation, and SEM analysis showed that the nanocomposites presented cavities around the nanoparticles after irradiation. Our results showed that incorporating CaO nanoparticles into the PLA polymer matrix allows future development of more sustainable materials as nanocomposites for food packaging or medical devices. © 2022